Workplace Bullying and Its Implications for Gender Transformation in the South African Higher Education Sector: An Intersectional Perspective. (23rd September 2022) - Mangolothi, Brightness; Pelisa Mnguni, Peliwe
Abstract : While transformation in the higher education sector in South Africa has been the subject of intensive research since 1994, few studies have explored the link between workplace bullying and transformation. Whereas workplace bullying has drawn researchers' attention for decades, it is only recently that scholars have started to interrogate the phenomenon through the intersectional lens. This paper employs intersectionality to explore women academics' experiences of workplace bullying and to suggest links between workplace bullying and gender transformation in the higher education sector in South Africa. Semi-structured interviews were conducted with a cross-section of 25 women academics who had experienced workplace bullying. As part of data triangulation, four union representatives and three human resources practitioners were also interviewed. The study's main findings indicate that gender, race and class mediate women academics' experiences of workplace bullying. In historically White universities, African, Coloured and Indian women academics, particularly those from working-class backgrounds, are more likely to be bullied, by seniors, peers, administrators and students. For White women academics, race ameliorates their workplace bullying experiences. The simultaneous effects of race, gender and class derail transformation as members of previously disadvantaged groups either remain stuck in junior academic positions, or exit the sector.